PEMBUATAN JENDELA OTOMATIS MENGGUNAKAN SENSOR CAHAYA - Muhammad Albet; Prama Wira Ginta; Aji Sudarsono (UNIVED Press, 2014)
Problem formulation of this research is to open and close the window automatically using a light sensor. Software that are used in this research includes operating systems, programming languages and data processing software. The Windows 7 was used as operating system. Programming language used was Basic - Bascom AVR and Visual Basic 6.0. The working principle of the automatic window using light sensor when the sensor exposed to bright light, the window will open automatically and vice versa, when the sensor is not a bright light, the window will be closed automatically.Keywords: Sensor (LDR) and Microcontroller